The proneural transcription factor Atoh1 promotes odontogenic differentiation in human dental pulp stem cells (DPSCs) - Camila Sabatini; Huey-Jiun Lin; Galib Ovik; Richard Hall; Techung Lee (BMC Molecular and Cell Biology)
Abstract Background Bioengineering of human teeth for replacement is an appealing regenerative approach in the era of gene therapy. Developmentally regulated transcription factors hold promise in the quest because these transcriptional regulators constitute the gene regulatory networks driving cell fate determination. Atonal homolog 1 (Atoh1) is a transcription factor of the basic helix-loop-helix (bHLH) family essential for neurogenesis in the cerebellum, auditory hair cell differentiation, and intestinal stem cell specification. The functional versatility of Atoh1 prompted us to test the possibility that Atoh1 may intersect the dental pulp stem cell (DPSC) gene regulatory network governing odontogenic differentiation. Methods We isolated DPSCs from human dental pulps and treated the cells with a replication-deficient adenoviral vector to achieve robust ectopic expression of Atoh1, following which the growth and odontogenic differentiation profiles of DPSCs were characterized. Results DPSCs harboring the Atoh1 expression vector exhibited an approximately 3,000-fold increase in the expression of Atoh1 compared to the negative control, leading to increased DPSC proliferation in the growth medium (P < 0.05). In the odontogenic medium, Atoh1 caused an early induction of BMP2 (P < 0.001) followed by a late induction of BMP7 (P < 0.01) and increased Wnt signaling (P < 0.01). The increased BMP/Wnt signaling led to up to 8-fold increased expression of the master osteogenic transcription factor Osterix (P < 0.005) while exhibiting no significant effect on Runx2 or Dlx5, which are abundantly expressed in DPSCs. Atoh1 stimulated expression of type I collagen (P < 0.005) and small integrin-binding ligand, N-linked glycoproteins (SIBLINGs) such as bone sialoprotein (P < 0.001), dentin matrix protein 1 (P < 0.05), dentin sialophosphoprotein (P < 0.005), and osteopontin (P < 0.001), resulting in increased dentin matrix mineralization (P < 0.05). The odontogenic phenotype is associated with metabolic remodeling marked by enhanced glycolytic flux and attenuated mitochondrial metabolic enzyme activities. Conclusions Atoh1, despite being a proneural transcription factor in development, possesses a novel odontogenic function upon ectopic expression in DPSCs. This in vitro study demonstrates a novel odontogenic mechanism mediated by ectopic expression of the transcription factor Atoh1 in human DPSCs. The finding may offer an innovative strategy for gene-based regeneration of the pulp-dentin complex.